2015
DOI: 10.1371/journal.pone.0141370
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Suppresses Twist to Induce Apoptosis in MCF-7 Breast Cancer Cells

Abstract: Quercetin is a dietary flavonoid which exerts anti-oxidant, anti-inflammatory and anti-cancer properties. In this study, we investigated the anti-proliferative effect of quercetin in two breast cancer cell lines (MCF-7 and MDA-MB-231), which differed in hormone receptor. IC50 value (37μM) of quercetin showed significant cytotoxicity in MCF-7 cells, which was not observed in MDA-MB-231 cells even at 100μM of quercetin treatment. To study the response of cancer cells to quercetin, with respect to different hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(89 citation statements)
references
References 38 publications
7
81
0
1
Order By: Relevance
“…Results presented in this article collect a great variety of antitumor actions of either quercetin or the mentioned strategies of combination, encapsulation and derived compounds. Cell growth inhibition, in addition to apoptosis stimulation, were the main processes described as quercetin mechanisms of action against HCC, properties that have also been observed in different tumors, such as non-small cell lung cancer [64] and breast cancer [65,66]. Although almost studies associated antiproliferative activity of quercetin with alteration of several pathways, Akt/mTOR and MEK1/ERK1/2 signaling routes were mostly found to be regulated by this flavonoid, either as free drug as well as encapsulated [23,24,27,38,42].…”
Section: Discussionmentioning
confidence: 95%
“…Results presented in this article collect a great variety of antitumor actions of either quercetin or the mentioned strategies of combination, encapsulation and derived compounds. Cell growth inhibition, in addition to apoptosis stimulation, were the main processes described as quercetin mechanisms of action against HCC, properties that have also been observed in different tumors, such as non-small cell lung cancer [64] and breast cancer [65,66]. Although almost studies associated antiproliferative activity of quercetin with alteration of several pathways, Akt/mTOR and MEK1/ERK1/2 signaling routes were mostly found to be regulated by this flavonoid, either as free drug as well as encapsulated [23,24,27,38,42].…”
Section: Discussionmentioning
confidence: 95%
“…Our results indicated that changes in p16, p21, CDK2, and CDK4 protein levels seemed to make a major contribution to quercetin‐induced G 0 /G 1 arrest in HL‐60 cells. Accordingly, quercetin‐induced G 0 /G 1 cell cycle arrest was also observed in hepatoma cells, leukemic T cells, and breat cancer cells …”
Section: Discussionmentioning
confidence: 89%
“…and MDAMB-231 cell line through the suppression of Twist via p38MAPK signaling pathway [14]. Genistein inhibits the growth of MDA-MB-231 by regulating the apoptosis related genes and up-regulation of Bax and p21WAF1 molecular pathways [15].…”
Section: Commentarymentioning
confidence: 99%
“…In-vitro studies using MDA-MB-231 cells showed that exposure to quercetin leads to an enhanced expression of Bax and cyt c release from mitochondrial membrane [13]. Quercetin also induces apoptosis in MCF-7and MDAMB-231 cell line through the suppression of Twist via p38MAPK signaling pathway [14]. Genistein inhibits the growth of MDA-MB-231 by regulating the apoptosis related genes and up-regulation of Bax and p21WAF1 molecular pathways [15].…”
mentioning
confidence: 99%